2015
DOI: 10.1002/pros.22949
|View full text |Cite
|
Sign up to set email alerts
|

A novel urinary long non‐coding RNA transcript improves diagnostic accuracy in patients undergoing prostate biopsy

Abstract: FR0348383 transcript in post-DRE urine may be a novel biomarker for detection of PCa with great diagnostic value, especially in the grey zone cohort. The application of FR0348383 score in clinical practice might avoid unnecessary prostate biopsies and increase the specificity of PCa diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…SChLAP1 increases with progression of PCa and predicts poor prognosis of patients with PCa [11, 12]. More importantly, these cancer-related lncRNAs can be detected in body fluids, such as blood and urine [13, 14], which makes them ideal diagnostic and prognostic biomarkers for cancer patients. However, previous studies focused mainly on the diagnostic value of SChLAP1 in tissue [15].…”
Section: Introductionmentioning
confidence: 99%
“…SChLAP1 increases with progression of PCa and predicts poor prognosis of patients with PCa [11, 12]. More importantly, these cancer-related lncRNAs can be detected in body fluids, such as blood and urine [13, 14], which makes them ideal diagnostic and prognostic biomarkers for cancer patients. However, previous studies focused mainly on the diagnostic value of SChLAP1 in tissue [15].…”
Section: Introductionmentioning
confidence: 99%
“…Given the altered expression of lncAPP in advanced PCa, we hypothesized a potential relationship with clinical outcomes. Our previous study demonstrated that circulating lncRNAs could exist in a stable form of fragments and urine sediments derived lncRNAs could be used as diagnostic marker of PCa . To examine whether lncAPP could be present in extracellular fluid, we extracted RNAs in urine sediments of PCa patients.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, lncRNAs have been not only studied in tumor tissue but have also been identified in the circulation in an increasing number of other cancers. For example, the lncRNA FR0348383 in urine improved diagnostic accuracy in patients undergoing prostate biopsy [19], FER1L4 was demonstrated to be present in human plasma and to be significantly down-regulated after surgery [20], and AA174084 was reported to have potential as a marker for early diagnosis of gastric cancer [21]. Although no systematic study has examined circulating lncRNAs in CRC patients, miRNAs, another class of non-coding RNA, have been widely studied in the circulation of CRC patients [22].…”
Section: Discussionmentioning
confidence: 99%